An Urban Form Study on Walking Choice (A Case Study in The Central Business District Jenderal Sudirman, Pekanbaru) - Ade Wahyudi; Febby Asteriani; Rona Muliana; Adam Raihan Aulia; Muhammad Fikri (Jurnal Planologi, 2023)
ABSTRACTUrban form and walking choice have complex relationships. Initial research has shown some drawbacks, uncertainties, and no inclusive results regarding the impact of urban form on walking choice since previous studies disregard walking purposes (utilitarian, transit, and non-utilitarian). The quantitative approach uses a statistical analysis and scoring index from the International Physical Activity and Environmental Project, while the qualitative approach applies a descriptive-analytic to describe travel behaviour and preference. The aims of this research are (1) to measure the walkability index with the urban forms approach, (2) to analyze the travel preference, travel behaviour for walking choice, (3) to see the effect of urban form on walking choice. The results showed that only two areas are walkable (Grid 2 with WAI 4,58 and Grid 5 with WAI 0,87). Meanwhile, the rest of the grids remained negative and had very low walkability indicators. Regarding walking preference, 63.40% of respondents contributed to non-active walking choice, whereas only 36.6% accounted for walking as their basic transportation mode. Interestingly, nearly 50% of walking preferences are done for non-utilitarian purposes since walking is still needed to keep their bodies healthy. Besides, the urban form variables have differently impacted on walking choice purposes. Firstly, walking for utilitarian purposes has been affected by entropy (P>{z} 0.049), floor area ratio (P>{z} 0.039), and household density (P>{z} 0.038). Therefore, walking for transit purposes has been influenced by connectivity (P>{z} 0.039), whereas walking for non-utilitarian purposes has been affected by household density (P>{z} 0.031).Keyword : surban form, utilitarian, transit, non-utilitarian, walkability ABSTRAKBentuk kota dan pemilihan moda berjalan kaki memiliki hubungan yang kompleks. Penelitian sebelumnya menunjukkan kelemahan, ketidakpastian, dan tidak adanya hasil yang jelas terkait bagaimana pengaruh bentuk kota terhadap pemilihan moda berjalan kaki. Hal ini disebabkan karena tidak mempertimbangkan jenis-jenis pelaku pejalan kaki (utilitarian, transit, non-utilitarin). Penelitian ini menggunakan metoda kombinasi, yaitu metoda kuantitatif dengan teknik analisis dan rumus indeks berjalan kaki dari IPEN Project dan analisis skoring untuk melihat klasifikasi tingkat berjalan kaki. Kemudian, metoda kualitatif menggunakan teknik analysis statistic deskriptif dengan distribusi frekuensi terkait perilaku perjalanan dan pemilihan moda transportasi. Penelitian ini bertujuan untuk (1) mengukur indeks berjalan kaki dengan pendekatan bentuk kota, (2) menganalisis pemilihan perilaku perjalanan, (3) menganalisis pengaruh bentuk kota terhadap pemilihan moda berjalan kaki. Hasil analisis terlihat bahwa hanya 2 area saja yang termasuk ramah bagi pejalan kaki (Grid 2 dengan WAI 4,58 dan Grid 5 dengan WAI 0,87). Kemudian, hanya 36.6% responden yang menjawab berjalan kaki sebagai moda transportasi utama, sementara sisanya menggunakan kendaraan. Menariknya, 50% responden berjalan kaki untuk tujuan olahraga dan rekreasi (non-utilitarian) dengan alasan menjaga tubuh agar tetap sehat. Variabel bentuk kota yang mempengaruhi pejalan utilitarian adalah entropi (P>{z} 0.049),, lantai bangunan (P>{z} 0.039),  dan kepadatan permukiman (P>{z} 0.038). Pejalan kaki transit hanya dipengaruhi oleh konektivitas (P>{z} 0.039) dan pejalan kaki non-utilitarian hanya dipengaruhi oleh kepadatan permukiman (P>{z} 0.031).Kata kunci : Bentuk kota, pejalan kaki utilitarian, transit, non-utilitarian, walkability